A Review of Career Guidance and Counselling Programs: Exploring the Impact of Career Guidance and Counselling on Decision-Making Process in High School Students (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The capacity of high school students to make decisions about their future occupations, as wellas their feeling of self-efficacy and their level of academic accomplishment, are all positively impacted bythe presence of guidance and counselling services in the schools in which they are enrolled. Studentsmay also benefit from these programmes by learning how to avoid making hasty or ill-informedprofessional judgements, as well as how to become more realistic and confident in their decisions.Another benefit of these programmes is that students may learn how to become more confident in theirdecisions by learning how to become more realistic. Helping people make informed decisions about theireducational and professional trajectories is one of the most important roles that may be played byprogrammes that provide career guidance and help to individuals. The primary objective of this researchis to investigate the impact that career assistance and counselling have on the decision-making process.In light of this, there is a growing need in today's rapidly changing labour market for the guidance andhelp of career counsellors.